GAMBARAN PENGETAHUAN BAHAYA MEROKOK TERHADAP KESEHATAN PADA SISWA SMA NEGERI 2 TONDANO - Refalia Clara Payow; Theo Mautang; Lucyana Pongoh (STIKES Columbia Asia Medan, 2024)
Cigarettes are tobacco products that are used by burning, smoking, or inhaling smoke produced by the plants Nicotiana tabacum, Nicotinia rustica, and other species or their synthesis. The smoke contains nicotine and tar, with or without additions. The goal of this study is to obtain an overview of SMA Negeri 2 Tondano students' understanding of the health risks associated with smoking. This study takes a quantitative approach. The data collection method is questionnaire instrument data. According to the study's findings, the vast majority of students, 93 (75.61%), had a high level of understanding of the consequences of smoking. The remaining 23 pupils (18.70%) were classified as high, 7 students (5.69%) as low, and no children were classified as very low, or 0%.